Overview of Emotional Intelligence (EI) of implementing nurses in providing nursing services in inpatient wards at hospitals - Mita, Mita; Tafwidhah, Yuyun; Maulana, M Ali (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Emotional intelligence is an important skill that health professionals such as nurses must possess. Emotional intelligence leads to mental health, self-care, and job satisfaction. The purpose of this study was to determine the level of emotional intelligence of nurses in the hospital, which consists of components of self-awareness, emotional management, motivation, empathy, and skills. Research Methodology: The research method was a quantitative survey involving 111 associate nurses from 10 treatment rooms selected using a purposive sampling technique. The research instrument used a nurse characteristics questionnaire and an emotional intelligence questionnaire. Result: The results showed that the characteristics of the respondents were primarily female. Namely, 70 nurses (63.1%) and the level of education in the nursing profession was higher than the Diploma but not much different, namely 59 and 50 respondents, respectively. The average age of respondents is 31 years, and the average length of work is 6.54 years. The results of nurses' emotional intelligence are at a high level, namely as much as 70.3%; high emotional intelligence can support the ability of nurses to provide nursing services. Nurses must consider emotional intelligence development. Conclusion: This can have a good impact on the nursing services provided. Nurses will reach bio-psycho-social and spiritual well-being. Implementing EI in nursing practice within inpatient wards is essential for enhancing the quality of care provided to patients and the well-being of nursing staff. Investing in training programs that foster emotional intelligence could significantly improve healthcare outcomes, reduce burnout, and create a more supportive work environment